KONTRIBUSI GAGASAN K.H. AHMAD DAHLAN DALAM DINAMIKA PENDIDIKAN DI KOTA PANGKAL PINANG - Hardiansyah Hardiansyah; Dendi Saputra; Ermawansyah Ermawansyah; Ifansyah Ifansyah; Jerry Prayoga; Aseliyanti Aseliyanti; Donna Oktaviani; Gita Septiana; Hafizia Puspitarini; Desfa Yusnaliana (Kuttab : Jurnal Ilmu Pendidikan Islam, 2022)
This article aims to find out the value of KH's struggle. Ahmad Dahlan and his ideas about education, and its relevance to the world of education, especially in Pangkalpinang. The Muhammadiyah organization has a foundation and a firm grip on the wheels of education in various remote areas. This article finds that Kyai Ahmad Dahlan's ideas are relevant to the development of education in Pangkalpinang City in integrating general and Islamic science, curriculum development, habituation of students, and improving the quality of education in educational institutions